1995
DOI: 10.1093/oxfordjournals.aje.a117613
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Nonsmoking Women in NHANES I and NHANES I Epidemiologic Follow-up Study with Exposure to Spouses Who Smoke

Abstract: Few studies have examined the relation between passive smoking and dietary intake in a large population. This report examines the nutrition and behavioral characteristics of 3,896 nonsmoking women from the first National Health and Nutrition Examination Survey (NHANES I) population in relation to exposure to environmental tobacco smoke. The data indicate that nonsmoking women who were exposed to husbands who smoked were more likely to be older, have lower education, live in the city, and have other health beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 0 publications
3
45
1
Order By: Relevance
“…Some previously published data are available about the associations of ETS exposure with socioeconomic status among non-smoking adults [14][15][16][17][18][19][20][21] and children. [22][23][24] These data either showed that ETS exposure was inversely associated with socioeconomic status, 14-17 22 23 or their evidence was equivocal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previously published data are available about the associations of ETS exposure with socioeconomic status among non-smoking adults [14][15][16][17][18][19][20][21] and children. [22][23][24] These data either showed that ETS exposure was inversely associated with socioeconomic status, 14-17 22 23 or their evidence was equivocal.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the studies involving adult populations did test for statistical significance and adjust for confounding. [14][15][16] Each of these studies reported moderate-to-strong inverse associations of ETS exposure with socioeconomic status. These studies were limited somewhat, however, by small sample size, 16 study populations restricted to women, 14 16 use of binary indicators only of socioeconomic status, 15 and lack of control for potential confounding by ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Steenland et al (45) found that the positive associations between serum cotinine and body mass index and the negative correlation with dietary carotenoids were greatly diminished by adjusting for age, sex, race, and education. Earlier studies of the prevalence of cardiovascular risk factors in relation to spousal smoking were too small to be informative (47)(48)(49)(50).…”
Section: Confoundingmentioning
confidence: 99%
“…For example, it is documented that non-smokers living with smokers have lower intakes of certain micronutrients (Matanoski et al, 1995). Sidney et al (1989) and Le Marchand et al (1991) estimated that the effect estimate for ETS and lung cancer would decrease from 2.0 to 1.8 after adjustment for b-carotene intake.…”
Section: Summary Of Effect From Authoritative Reports and Meta-analysesmentioning
confidence: 99%